Pengembangan Instrumen Supervisi Guru Al-Qur'an dalam Meningkatkan Mutu Pembelajaran Al-Qur'an di SDIT Nurul Fikri Depok - Aminulloh, Aminulloh; Sastradihardja, EE. Junaedi; Susanto, Susanto (ISLAMIC PEDAGOGY: Journal of Islamic Education, 2024)
This research is research that aims to find out how the development of Al-Qur'an teacher supervision instruments can improve the quality of Al-Qur'an learning at SDIT Nurul Fikri Depok, West Java. This research uses an exploratory research method by carrying out a qualitative analysis approach. Data collection was carried out through; observation, interviews and documentation studies. The data sources and informants in this research were the school principal, the person in charge/coordinator of the Al-Qur'an teacher at the school, as well as several Al-Qur'an teachers. Data analysis using reduction, presentation and verification. The results of the research show that: (1) Indicators of the quality of Al-Qur'an learning at SDIT Nurul Fikri Depok include; planning, implementation and evaluation that can improve the quality of students' Al-Qur'an learning with indicators of good and correct quality in makhorijul letters and recitation, as well as having fluency in reading the Al-Qur'an. So that the planning, implementation and evaluation process indicators will produce outputs, outcomes and impacts on the quality of Al-Qur'an learning. (2) The steps for developing Al-Qur'an teacher supervision instruments can be identified through several stages or steps starting from determining the problem and what instruments will be used. Determine the variables and indicators that will be monitored, determine the instruments that will be used. Explaining each variable, compiling the instrument grid, writing instrument statement items, reviewing the instrument, compiling a temporary set of instruments, carrying out trials so that it can be seen whether the instrument can be administered, whether each item of the instrument can be understood by the person being supervised and knowing the validity and reliability. Repairing instruments according to test results, as well as rearranging instrument devices to obtain data and information that will be used. (3) The role of developing Al-Qur'an teacher supervision instruments in ensuring the quality of Al-Qur'an learning at SDIT Nurul Fikri Depok is very important. The development of academic supervision instruments to improve quality has often been carried out at SIT Nurul Fikri by the P3TK bureau under the SDMO division of SIT Nurul Fikri. Development is carried out as a follow-up to the results of supervision which is routinely carried out three times every semester, both scheduled and unscheduled. In an effort to improve the quality of Al-Qur'an learning, the results of supervision are monitored and checked by the SIT Nurul Fikri quality assurance team by carrying out; Plan-Organizing-Actuating-Controlling (POAC). By planning, organizing, implementing and monitoring and developing educational quality standards consistently and sustainably, the aim is to provide service satisfaction to both internal and external stakeholders.